2022
DOI: 10.5582/ddt.2022.01022
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response of smokers to the COVID-19 vaccination: Evaluation based on cigarette dependence

Abstract: SARS-CoV-2, COVID-19, mRNA vaccine, anti-RBD IgG level, cigarette dependence Smokers may have lower antibody titers after vaccination with a coronavirus disease 2019 (COVID-19) mRNA vaccine. However, to the best of our knowledge, no study has evaluated antibody titers after COVID-19 vaccination based on the level of smokers' cigarette dependence. In this study, we measured the level of serum anti-severe acute respiratory syndrome coronavirus 2 (anti-SARS-CoV-2) spike protein receptor-binding domain (S-RBD) imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…As secondary factors modulating the vaccine-induced antibody response to SARS-CoV-2, we gathered additional information on the BMI and smoking habits of the study subjects. Contrary to the literature [ 10 , 37 ], the active smokers did not seem to build up significantly lower anti-S-RBD Ig antibody concentrations compared with the study subjects who had quit smoking or were never-smokers, which could be explained by the overall small number of active smokers in each group. Strikingly, in our study, overweight triple-vaccinated subjects with a BMI > 30 demonstrated significantly higher anti-S-RBD Ig antibody concentrations compared with normal-weight study subjects, which conflicts with several other available studies [ 12 , 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…As secondary factors modulating the vaccine-induced antibody response to SARS-CoV-2, we gathered additional information on the BMI and smoking habits of the study subjects. Contrary to the literature [ 10 , 37 ], the active smokers did not seem to build up significantly lower anti-S-RBD Ig antibody concentrations compared with the study subjects who had quit smoking or were never-smokers, which could be explained by the overall small number of active smokers in each group. Strikingly, in our study, overweight triple-vaccinated subjects with a BMI > 30 demonstrated significantly higher anti-S-RBD Ig antibody concentrations compared with normal-weight study subjects, which conflicts with several other available studies [ 12 , 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Another fact is that the smoking rate in non-infected HCWs was higher than that in infected ones. It was reported that infected patients who smoke have a lower antibody response, which is a risk factor for severe SARS-CoV-2 infection; the frequency in hospitalized patients was lower than in the normal population [24,42,43]. In our cohort of HCWs, we saw a paradox of smokers being in the non-infected HCWs group.…”
Section: Discussionmentioning
confidence: 48%
“…Recent studies have found a negative association between smoking and SARS-CoV-2 mRNA vaccine-induced antibody responses. Current smokers show lower antibody titers after vaccine administration and a faster decline in antibody levels over time than non-smokers [29,30]. Furthermore, a Japanese study found that antibody responses declined with increasing cigarette dependence [29].…”
Section: Original Articlementioning
confidence: 99%